ANALISIS MOTIVASI PETANI DALAM MENANAM KOPI SANGGABUANA DI KABUPATEN KARAWANG (STUDI KASUS DESA MEKARBUANA KECAMATAN TEGALWARU) - I Putu Eka Wijaya; Suhaeni Suhaeni; Luthfi Nur ’Azkiya (Universitas Wahid Hasyim, 2019)
Sanggabuana coffee is a well known Robusta type coffee that has been cultivated in Karawang for years. This commodity has a high tolerance to diseases and has high caffeine, but in some ways has a cheaper price than Arabica type coffee. However, Sanggabuana coffee has been widely cultivated in Karawang and being the main commodity unique to Karawang. The purpose of this research is to know how high the motivation of the farmer to cultivate Sanggabuana coffee and the connection to the farmer motivation on the social-economic factor of cultivating Sanggabuana coffee. This research will be conducted in Karawang district (Case Study of Mekarbuana village, Tegalwaru sub-district) West Java, Indonesia, Using Primer dan secondary data set. Primer data gathered by direct interview to the farmer or selected respondents as a sample. Generally, respondents consist of the producer or Sanggabuana coffee farmer. Secondary data obtained from the department of agriculture in Karawang district, local agencies, and another related department. The sample is selected using Simple Random Sampling (SRS). The analysis method used in this research is Likert’s Summated Ratings and Spearman Rank Correlation. High motivation and social-economic that correlated to the level of education, experienced in farming and the number of family dependent possessed by the farmer as the result of this research. Keywords: Motivation, Sanggabuana coffee, Correlation.